2020
DOI: 10.1073/pnas.2009680117
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP3 inflammasome inhibitor OLT1177 rescues cognitive impairment in a mouse model of Alzheimer’s disease

Abstract: Numerous studies demonstrate that neuroinflammation is a key player in the progression of Alzheimer’s disease (AD). Interleukin (IL)-1β is a main inducer of inflammation and therefore a prime target for therapeutic options. The inactive IL-1β precursor requires processing by the the nucleotide-binding oligomerization domain-like receptor family, pyrin domain containing 3 (NLRP3) inflammasome into a mature and active form. Studies have shown that IL-1β is up-regulated in brains of patients with AD, and that gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(124 citation statements)
references
References 72 publications
2
122
0
Order By: Relevance
“…As shown recently, cytokines up-regulate γ-secretase activity for Aβ production through expression of γ-secretase modulatory protein IFITM3 (interferon-induced transmembrane protein 3) in neurons and astrocytes [ 45 ]. Accordingly, blocking microglial inflammasome by the inhibitor dapansutrile (OLT1177) reduced microglia activity and cortical Aβ plaque deposition, and rescued cognitive function in AD mouse model [ 46 ]. In the early stage of AD, activated microglia cells remove cerebral Aβ deposits.…”
Section: Alzheimer’s Disease—toxic Amyloid-β Proteins and Triggered Neuropathogenic Phenomenamentioning
confidence: 99%
“…As shown recently, cytokines up-regulate γ-secretase activity for Aβ production through expression of γ-secretase modulatory protein IFITM3 (interferon-induced transmembrane protein 3) in neurons and astrocytes [ 45 ]. Accordingly, blocking microglial inflammasome by the inhibitor dapansutrile (OLT1177) reduced microglia activity and cortical Aβ plaque deposition, and rescued cognitive function in AD mouse model [ 46 ]. In the early stage of AD, activated microglia cells remove cerebral Aβ deposits.…”
Section: Alzheimer’s Disease—toxic Amyloid-β Proteins and Triggered Neuropathogenic Phenomenamentioning
confidence: 99%
“…In vitro and in vivo studies have shown that Aβ peptide activates NLRP3 inflammasome in microglial cells. Furthermore, in a mouse model of AD, NLRP3 knockout (KO) mice were protected from impaired spatial memory performance and showed a decrease in the Aβ plaque load [ 67 ], similar results were obtained when a specific NLRP3 inhibitor was administered to mice [ 68 ]. This evidence points to the inflammasome as a potential therapeutic target for AD treatment [ 69 ].…”
Section: Curcumin Oxidative Stress and Inflammationmentioning
confidence: 88%
“…Administration of OLT1177, an NLRP3 inflammasome inhibitor, rescued cognitive impairment and neuroinflammation in an APP/PS1 mouse model of Alzheimer’s disease (Lonnemann et al 2020 ). Activation of the NLRP3 inflammasome was increased in CRND8 APP transgenic mice, an Alzheimer's disease mouse model, compared to nontransgenic littermate controls, and treatment with JC-124, another NLRP3 inflammasome inhibitor, led to a decrease in amyloid-β deposition in the brain of CRND8 transgenic mice (Yin et al 2018 ).…”
Section: Nlrp3 Inflammasome-associated Diseasesmentioning
confidence: 99%